BOOK SALES SYSTEM DESIGN ON FOUNDATION AKUBACA - Evi Novianti; Sahni Damerianta, Skom, MM (Jurnal Sistem Informasi, 2003)
In a company or organization that wants its business continues to grow, the success ofthe company's business development is a measure of the success of the company. Ifyou want the performance will be maintained, they should be able to mobilize all itsoperational resources to work optimally. One is the staff who work behind the dataand information processing. This is due to make the right decisions requires accurate,easily understandable and fast. This is where the role of a database applicationprogram, the provider of computerized data that should be able to provideinformation within a short and easy to read.The author found the case while working as a translator at a book publisher AkubacaFoundation semimanual still using the system in data processing sales. Therefore,transactions that occur must be managed effectively. The author designed the booksales system that meets their needs using Visual Basic 6-based database.